2019
DOI: 10.1186/s12870-019-1891-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and functional analysis of oleosin genes in Brassica napus L.

Abstract: Background: Rapeseed is the third largest oil seed crop in the world. The seeds of this plant store lipids in oil bodies, and oleosin is the most important structural protein in oil bodies. However, the function of oleosin in oil crops has received little attention. Results: In the present study, 48 oleosin sequences from the Brassica napus genome were identified and divided into four lineages (T, U, SH, SL). Synteny analysis revealed that most of the oleosin genes were conserved, and all of these genes experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 67 publications
1
46
1
Order By: Relevance
“…Four Brassica napus oleosin genes were overexpressed in Arabidopsis increased the linoleic acid content (13.3% at most) and the seed weight. In the meanwhile, the eicosaenoic acid content decreased by 11% in seeds of transgenic lines (Chen et al, 2019). The experimental evidence confirmed that oleosins play important roles in regulating lipid metabolization.…”
Section: Oleosins Regulate Lipid Metabolizationmentioning
confidence: 53%
“…Four Brassica napus oleosin genes were overexpressed in Arabidopsis increased the linoleic acid content (13.3% at most) and the seed weight. In the meanwhile, the eicosaenoic acid content decreased by 11% in seeds of transgenic lines (Chen et al, 2019). The experimental evidence confirmed that oleosins play important roles in regulating lipid metabolization.…”
Section: Oleosins Regulate Lipid Metabolizationmentioning
confidence: 53%
“…Previous studies have shown that oleosin was accumulated in a coincident manner with TAG accumulation and the abundant expression of oleosin was associated with relatively high oil content in seeds [ 48 53 ]. For example, overexpression of OBO genes in transgenic plant seeds increased oil content by up to 46% as compared to the non-transgenic controls [ 54 , 55 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…2). DsRed, as a selectable marker gene for transgenic seed screening, is advantageous for separating transgenic and non-transgenic seeds in many plants, such as Arabidopsis, rice and Camelina sativa [15,47,48]. In Arabidopsis, DsRed has been used as a visual selection marker to promote transgenic seed screening [33,49,50].…”
Section: Discussionmentioning
confidence: 99%